PENGARUH PRICE DISCOUNT TERHADAP PEMBELIAN IMPLUSIF PADA FITUR SHOPEE LIVE MELALUI KUALITAS PRODUK SEBAGAI VARIABEL INTERVENING - Wiryaatmaja , Christopher Louis; Adryan Rachman (Jurnal Nusa Manajemen, 2025)
This study aims to analyze the effect of Price Discount on Impulse Buying with Product Quality as a mediating variable among Shopee Live users in Tangerang City. The research employs a quantitative approach with Structural Equation Modeling (SEM) using SmartPLS 4.0. Data were collected via an online questionnaire involving 200 respondents. The results indicate that Price Discount has a positive but not significant direct effect on Impulse Buying. However, when mediated by Product Quality, Price Discount significantly influences Impulse Buying. The path coefficient of 0.344 indicates that positive perceptions of product quality strengthen the relationship between price discounts and impulsive purchase decisions. The implications of this study emphasize the importance of combining discount strategies with product quality improvements to encourage impulse buying. E-commerce companies like Shopee Live are advised to ensure that discounted products maintain high quality to foster consumer satisfaction and trust. Furthermore, urgency-based promotions and transparent product information can enhance the effectiveness of price discounts. This research is limited by the number of respondents and platform scope; future studies should expand the coverage and incorporate additional relevant variables.